Metabolic disposition of WTX101 (bis-choline tetrathiomolybdate) in a rat model of Wilson disease. (4th March 2019) - Plitz, Thomas; Boyling, Lee
Abstract: 1. WTX101 (bis-choline tetrathiomolybdate) is an investigational copper (Cu)-protein-binding agent developed for the treatment of Wilson disease (WD), a rare genetic disorder caused by mutations in the ATP7B Cu-transporter and resulting in toxic Cu accumulation. 2. Mass balance of a single intravenous WTX101 dose, measured as molybdenum (Mo), was assessed over 168 h in control (Long Evans Agouti [LEA]) and Long-Evans Cinnamon (LEC) rats, a WD model. 3. In LEC rats, Mo was partially excreted (up to 45%); 29% by renal clearance, and faecal clearance, still ongoing at 168 h, accounted for 16%. In contrast, in LEA rats, Mo was almost fully excreted (∼87%); 79% was renally cleared with only 7% faecal excretion. 4. In LEC rats, the proportion of faecal to renal Mo excretion was enhanced (4:6) compared to controls (1:9). 5. Substantially more Mo was found in LEC liver and kidney compared with LEA tissues, in line with tissue Cu distribution. 6. These findings are consistent with the WTX101 mechanism of action: in the WD model, excess Cu is removed from hepatic metallothionein and retained within the stable tetrathiomolybdate-Cu-albumin tripartite complex, preventing tetrathiomolybdate degradation and resulting in less urinary elimination and greater faecal excretion than in controls.